Estetika Warna Kulit Manggis dalam Seni Lukis - I Nengah Wirakesuma; I Wayan Mudana; I Ketut Mustika; I Wayan Kondra (Journal on Education, 2025)
The aesthetics of mangosteen skin color have unique characteristics compared to other synthetic colors. Aesthetic and dimensional, mangosteen skin color displays natural shades such as light brown, chocolate, brownish, red, purple, and blue. Painting using mangosteen peel is a creative process that begins with picking mangosteen fruit from the garden. Coincidentally, the author became interested in scratching spontaneously. When he split a mangosteen fruit into two equal parts, the author used the mangosteen peel to create a graffiti on the canvas. This technique involves spontaneous movements of the fingers, pressing gently, moderately, and sometimes hard on the canvas. The resulting color effect appears naturally, according to the intensity of the finger movement when scratching the mangosteen skin on the canvas. The painting method using mangosteen peel is carried out spontaneously, following the stages of art creation: existence, exploration, experimentation and evaluation. The creation of paintings using mangosteen peel reflects a creation process that uses fine art elements of light, point, line, space, plane, color, texture and composition. The resulting works of art are titled as line aesthetics: Line Aesthetic 1, Line Aesthetic 2, Line Aesthetic 3, and so on. The use of mangosteen peel color as an alternative medium in painting is driven by the need for creativity to achieve works of art that are new, high quality, meaningful and have high harmonious value.